Impact of reproductive factors on breast cancer incidence: Pooled analysis of nine cohort studies in Japan. (1st March 2021) - Takeuchi, Taro; Kitamura, Yuri; Sobue, Tomotaka; Utada, Mai; Ozasa, Kotaro; Sugawara, Yumi; Tsuji, Ichiro; Hori, Miyuki; Sawada, Norie; Tsugane, Shoichiro; Koyanagi, Yuriko N.; Ito, Hidemi; et al.
Abstract: Prior studies reported the association of reproductive factors with breast cancer (BC), but the evidence is inconsistent. We conducted a pooled analysis of nine cohort studies in Japan to evaluate the impact of six reproductive factors (age at menarche/age at first birth/number of births/age at menopause/use of female hormones/breastfeeding) on BC incidence. We conducted analyses according to menopausal status at the baseline or at the diagnosis. Hazard ratio (HR) and 95% confidence interval (CI) were estimated by applying Cox proportional‐hazards model in each study. These hazard ratios were integrated using a random‐effects model. Among 187, 999 women (premenopausal: 61, 113, postmenopausal: 126, 886), we observed 873 premenopausal and 1, 456 postmenopausal cases. Among premenopausal women, use of female hormones significantly increased BC incidence (HR: 1.53 [1.04–2.25]). Although P value for trend was not significant for age at first birth and number of births (P for trend: 0.15 and 0.30, respectively), women giving first birth at ages ≥36 experienced significantly higher BC incidence than at ages 21–25 years, and women who had ≥2 births experienced significantly lower BC incidence than nulliparous women. Among postmenopausal women, more births significantly decreased BC incidence (P for trend: 0.03). Although P value for trend was not significant for age at first birth and age at menopause (P for trend: 0.30 and 0.37, respectively), women giving first birth at ages 26–35 years experienced significantly higher BC incidence than at ages 21–25 years, and women with age at menopause: ≥50 years experienced significantly higher BC incidence than age at menopause: ≤44 years. BC incidence was similar according to age at menarche or breastfeeding history among both premenopausal and postmenopausal women. In conclusion, among Japanese women, use of female hormones increased BC incidence in premenopausal women, and more births decreased BC incidence in postmenopausal women.